The use of different cost of equity models when valuing SMEs: A case study - António Gomes; Maria João Jorge; Ana Gonçalves Pereira (Small Business International Review)
This study examines the valuation process of small and medium-sized enterprises (SMEs), using a Portuguese SME as a case study. The analysis focuses on calculating the cost of equity, with particular attention to the unique characteristics of these companies. The valuation was conducted using the discounted cash flow (DCF) method, with a preference for the average cost model. Two different approaches were employed to forecast free cash flows: (a) the geometric growth rate of sales, and (b) free cash flow projections derived from a model based on historical results. To calculate the cost of equity, three distinct models were used: (a) the capital asset pricing model (CAPM) with modifications proposed by Damodaran (2014), (b) the model developed by the Spanish Association of Accounting and Business Administration (AECA) from Rojo-Ramírez et al. (2012), and (c) the build-up model proposed by Ibbotson. These models serve as alternatives to the traditional CAPM, which is less suitable for unlisted companies due to the absence of a market beta. The study compares the results obtained from each model, focusing on their impact on the company’s valuation. Valuing SMEs is crucial for enhancing corporate decision-making. Furthermore, the approaches utilized in this study provide valuable guidelines for financial analysts involved in SME valuation.